Analysis of the Utilization of Rice Bran on Changes in Total Blood Cholesterol Concentration; An Update Systematic Review - St. Nur Azizah; Abdul Razak Thaha; Abdul Salam; Healthy Hidayanty; Citrakesumasari; Fridawaty Rivai (PT FORMOSA CENDEKIA GLOBAL, 2023)
The prevalence of coronary heart disease in Indonesia increased from 0.5% in 2013 to 1.5% in 2018. The risk factor is most commonly found to be an increase in cholesterol. The increase in cholesterol can be overcome by utilizing processed bran oil (RBO) as a supplement. The purpose of this systematic review is to examine the effectiveness of bran oil against changes in total blood cholesterol concentration based on dosage.This systematic review method is carried out based on the PRISMA flow diagram. The literature eligibility criteria are determined based on the PICOS framework. Literature searches and searches are conducted on the Crossref, DOAJ, Google Scholar, ProQuest, PubMed, and Science Direct databases. The screening stage is carried out with the help of the Mendeley application. Data extraction results are analyzed by searching for equations, comparisons and synthesizing data. The results of five selected articles and all of them show that consuming RBO has an effect on changes in total blood cholesterol concentrations. There are four articles using the RCT design and one article using the experimental design. The preparations and doses identified were RBO preparations at a dose of 45 ml/day and gamma-oryzanol-rich RBO at a dose of 15 ml/day (20.000 ppm gamma-oryzanol). RBO consumption is effective against changes in total blood cholesterol concentration with the use of different doses. We recommend that the next systematic review can examine the effects of various doses of bran oil using meta-analysis